Percepção ambiental e representação social de jovens estudantes do município de Santos na região costeira de São Paulo - um estudo de caso sobre trilhas urbanas ambientais - Santana, Arnaldo da Silva [UNIFESP] (2018)
The environment has been a relevant issue for many decades in the world and for Brazil and the implementation of Environmental Education (EE) is related to the development of these socio-environmental issues, due to the important role of education in resolving this problem. However, EE is universalized in 94% of primary schools in our country, according to the Ministry of Education, the work developed, in general, has not yet reached the level of quality and reflection sought. From this perspective, it can be observed that, although Brazilian legislation proposes that EE should be present in schools in a transversal and interdisciplinary way, the reflections discussed above may bring us some questions. Thus, based on the concepts of Complex Environmental Education, the present study is aimed to evaluate the possible transformations in the environmental perceptions and social representations of the students after participating in different sensitization activities, among them the trek through an urban track. through attentive environmental perception, to reduce distances between human beings and nature. This study had a mixed results, being a research approach that combines both qualitative and quantitative forms. After applying the pedagogical activities diversified by the teacher / researcher, it is concluded that in particular the urban trail can be an important and cheap resource to be developed in places and schools with little financial resources, favoring the environmental perception and a more critical reflection of the reality socio-environmental where the activity is developed, although for the resignification of the social representations regarding the environment, it is necessary to keep a continuous and transversal work ahead so that there is effective change in the Central Nucleus of the Representation.